CONCENTRATION OF SOLUBLE LEPTIN RECEPTOR IN POPULATION - Bartek, Josef; Stejskal, David; Stejskal, Pavel; Oral, Ivo (Biomedical papers, 2000)
Examinations were performed in 568 probands (217 men, 351 women) selected randomly from healthypopulation according to the following criterion: no treatment in the last six weeks for any disease. All probandswere subjected to determination of BMI, cholesterol, triacylglycerols, LDL-cholesterol, intact proinsulin, insulin,uric acid, ALT, AST, GMT, LD, CRP, aterogenic plasma index, leptin, and soluble leptin receptor. We determinedconcentration of soluble leptin receptor in population sample of 560 probands. A positive correlation betweenleptinemia and BMI value was confirmed. It was found that Ob-Re concentration did not correlate with commonanthropometrical parameters nor leptin concentration in the serum, but correlated negatively only with insulin andplasma aterogenity. This finding indicates an increased presence of free leptin in patients with signs of insulin(therefore also leptin) resistance.
Keywords: Leptin receptor / Concentration of leptin receptor in population